2012
DOI: 10.1155/2012/909315
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Endothelial Function and Uterine Artery Doppler Velocimetry between Pregnant Women with or without Preeclampsia Development

Abstract: Background. Poor placentation and systemic endothelial dysfunction have been identified as main events in Preeclampsia (PE). The relationship and chronology of these phenomena are important if we are to understand the pathophysiological mechanisms underlying this major clinical problem. Objectives. To compare the evolution of placentation and endothelial function in normotensive and preeclamptic pregnancies. Patients and methods. In a prospective cohort study, 59 pregnant women with a high risk of developing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In 2003, Takase et al, applying FMD in a group of pregnant women at the end of the second gestational trimester, found sensitivity values close to 90%; however, those authors did not differentiate between the two clinical presentations of PE (late and early) ( 17 ) . Other studies have demonstrated that the FMD values are significantly reduced at the end of the second trimester in pregnant women who later develop either late or early PE ( 18 , 19 ) . The association of FMD with Doppler flowmetry of uterine arteries also presented good results in the prediction of PE ( 20 ) .…”
Section: Discussionmentioning
confidence: 96%
“…In 2003, Takase et al, applying FMD in a group of pregnant women at the end of the second gestational trimester, found sensitivity values close to 90%; however, those authors did not differentiate between the two clinical presentations of PE (late and early) ( 17 ) . Other studies have demonstrated that the FMD values are significantly reduced at the end of the second trimester in pregnant women who later develop either late or early PE ( 18 , 19 ) . The association of FMD with Doppler flowmetry of uterine arteries also presented good results in the prediction of PE ( 20 ) .…”
Section: Discussionmentioning
confidence: 96%
“…This observation was supported by the Brandao AHF et al . (2012)[ 4 ] study, in which FMD was performed twice for a patient, first at 16–20 weeks and second at 24–28 weeks of gestational age. They found that the group of patients who did not develop preeclampsia had shown an increase in FMD (74.2 ± 184.2%) value, while the group of patients who developed preeclampsia had shown a decrease (16.6 ± 38.2%) in the value of FMD ( P = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…As regards FMD, its utilization alone late in the second gestational trimester could identify approximately 90% of cases of PE, in a study developed by Takase et al (17) . The FMD results are significantly poorer in patients with late development of PE as from the 24th gestational week (18,19) . The association between the indirect evaluation of the endothelial function by FMD and of the placental perfusion by Doppler flowmetry of uterine arteries has proved to be highly accurate in the prediction of PE.…”
Section: Discussionmentioning
confidence: 99%